Inverse prognostic impact of ErbB2 mRNA and protein expression level in tumors of soft tissue sarcoma patients - Wichmann, Henri; Guettler, Antje; Bache, Matthias; Taubert, Helge; Vetter, Martina; Wurl, Peter; Holzhausen, Hans J.; Eckert, Alexander W.; Kappler, Matthias; Vordermark, Dirk (Strahlentherapie und Onkologie, 2014)
Human epidermal growth factor receptor 2 (ErbB2) is overexpressed in a variety of human malignancies. Moreover, ErbB2 has been reported to influence cancer patient survival and progression of different tumor entities. However, information regarding the prognostic impact of ErbB2 in soft tissue sarcoma (STS) patients is limited and conflicting.ErbB2 mRNA and protein levels were defined by quantitative real-time PCR and enzyme-linked immunosorbent assay (ELISA), and the prognostic impact of ErbB2 mRNA and protein levels in tumor tissue of 124 soft tissue sarcoma patients were investigated.The median ErbB2 mRNA expression level in tumor tissue was decreased 3.9-fold compared to non-neoplastic surrounding tissue (p = 0.001). Furthermore, an increased ErbB2 mRNA expression level was associated with an improved tumor-specific survival (p = 0.01, log rank test). Multivariate Cox's proportional hazard regression analyses revealed an increased ErbB2 mRNA expression level as an independent favorable prognostic factor for tumor-specific survival of STS patients (n = 124; RR = 3.0; 95 % CI = 1.6-5.7; p < 0.001). In addition, multivariate Cox's proportional hazard regression analyses showed that an increased ErbB2 protein expression level correlated with poorer recurrence-free survival of STS patients (n = 47; RR = 9.9; 95 % CI = 1.7-59.7; p = 0.012), in particular for STS patients who received postoperative radiotherapy (n = 27; RR = 17.9; 95 % CI = 1.3-247.7; p = 0.031).This study suggests an inverse prognostic value of ErbB2 mRNA and protein expression level.
EVALuna2:16311